Special issue: Land Use and Sustainable Mobility - Meurs, Henk (European Journal of Transport and Infrastructure Research, 2003)
Concerns about the sustainability of current land use and transportation practices are increasingly issues of policy concern in most countries of the world. There is a call for better coordination between land use and transport. A number of factors motivate such attention (Gorham, 1998) Firstly, growth in car ownership and use show no signs of abating. Secondly, technology seems unable to fully solve the environmental and other problems associated with motorized transport. Problems have remained with respect to CO2, noise and the nonemissions related impacts of vehicles. Thirdly, the building costs of new infrastructure have increased, whereas the benefits provided by such infrastructure, are increasingly questioned (Cervero, 2003). In cases where new road infrastructure is provided primarily to relieve congestion, these roads tend to provide at best only temporary relief. The increased capacity tends to induce new traffic in the relatively short run through spatial, temporal, and modal changes in travel patterns and, in the longer run, through land-use changes caused by changes in overall accessibility levels (Downs 1992; Goodwin, 1996). These insights have increased the attention for measures other than infrastructure construction (Banister, 2002). Fourthly, just one strategy, e.g. completely based on technology or pricing, cannot solve the problems alone. For example, price signals, clearly being a necessary part of any strategy to restrain the growth of car use, cannot be relied upon as the sole element of this strategy. Substantial increases in the cost of car use would be required for having a meaningful change in travel behavior, technology acquisition, or a restructuring of social activities. This appears to have insufficient public and political support.